201 Regulation of INOS Function, Redox State and NRF2 Activation by Macrophage GCH1 and Tetrahydrobiopterin. - McNeill, E; Crabtree, M; Sahgal, N; Chuaiphichai, S; Patel, J; Hale, A; Channon, K (2014)
: Tetrahydrobiopterin (BH4) is an essential co-factor for NO production from NOS enzymes. When BH4 levels become limiting these enzymes can become 'un-coupled', leading to superoxide production. GTP cyclohydrolase I (GTPCH), encoded by GCH1, is an essential enzyme in the biosynthesis of BH4. BH4 deficiency has been been shown to cause endothelial dysfunction and to exacerbate atherosclerosis in experimental models. However, the role of BH4 in regulating iNOS activity in leukocytes, and the potential impact of this on atherosclerosis is less clear. We have utilised a novel transgenic mouse to address the role of BH4 and iNOS in macrophage biology. We designed mice harbouring a 'floxed' portion of the GCH1 locus within the active site of the enzyme (GCHfl/fl mice). We crossed these with mice expressing the cre enzyme under control of the Tie2 promoter (GCHfl/fl Tie2cre). Cre expression causes efficient excision of the floxed allele in all leukocytes and endothelial cells, as detected by PCR for the floxed or knockout allele. To examine the effects of BH4 deficiency on macrophage biology and iNOS activity we utilised bone marrow derived macrophage cultures and compared un-activated macrophages with iNOS-expressing inflammatory macrophages. Bone Marrow Derived Macrophages cultured from GCHfl/fl mice show GTPCH protein expression and BH4 production, but have no iNOS expression. Stimulation with Lipopolysaccharide and Interferon-γ increases BH4 production and also induces iNOS protein expression and NO-derived nitrite accumulation. GCHfl/fl Tie2cre cells show no GTPCH protein expression and barely detectable levels of BH4 and, despite normal iNOS protein levels following stimulation, exhibit no nitrite accumulation. Furthermore GCHfl/fl Tie2cre BMDM show enhanced ROS production, as measured by DHE-HPLC. Intracellular BH4 levels can be rescued by treatment with the precursor sepiapterin, which also restores iNOS-mediated nitrite production and reduces ROS production by the macrophages. Gene array analysis of GCHfl/fl Tie2cre vs wildtype macrophages demonstrated only minimal genotype associated changes. However macrophages treated with LPS and Interferon-γ showed significant changes in 74 genes (passing FDR <5%) as a result of genotype. Pathway analysis of these genes revealed decreased upstream activation of nrf2. Decreased expression of nrf2 dependent genes was confirmed by qRT-PCR.